Answers

2015-06-06T22:06:27+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
5-3x = 2x²
A quadratic equation is in the form: ax²+bx+c=0 so:
0=2x²+3x-5 
This is already in standard form but I will further simplify it:
We use the quadratic equation:
x = -3 ± √(3²+40) = -3 ± 7 = 1 or -5/2
              4                 4
If you want the factors:
We have: (x-1)(x+5/2) so we need to multiply this by 2 since the value of a is 2:
2x
²+3x-5=(x-1)(2x+5)

0